2020
DOI: 10.21203/rs.3.rs-101162/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development and Validation of Multicenter Predictive Nomograms for Locally Advanced Pancreatic Cancer after Chemoradiotherapy

Abstract: Background: Due to common practice of hypofractionated radiotherapy in pancreatic cancer and heterogeneous chemotherapy regimens in previous studies, modified nomograms are required. Therefore, we aim to develop and validate prognostic nomograms for locally advanced pancreatic cancer (LAPC) after stereotactic body radiation therapy (SBRT) and chemotherapy.Methods: The development cohort comprised 925 patients with LAPC receiving SBRT and gemcitabine-based chemotherapy in our center, while 297 patients from ano… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It is challenging to put a single indicator into clinical practice, even though the risk score shows the potential to be regarded as a promising predictor of clinical outcomes in osteosarcoma patients 55 . Predictions made using the nomogram are more accurate and useful since they can take into account the relative importance of each variable 56,57 . Therefore, we integrated the risk score and other clinicopathological parameters to develop a nomogram.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is challenging to put a single indicator into clinical practice, even though the risk score shows the potential to be regarded as a promising predictor of clinical outcomes in osteosarcoma patients 55 . Predictions made using the nomogram are more accurate and useful since they can take into account the relative importance of each variable 56,57 . Therefore, we integrated the risk score and other clinicopathological parameters to develop a nomogram.…”
Section: Discussionmentioning
confidence: 99%
“…55 Predictions made using the nomogram are more accurate and useful since they can take into account the relative importance of each variable. 56,57 Therefore, we integrated the risk score and other clinicopathological parameters to develop a nomogram. The results indicated that the AUC values of ROC curves were significantly higher compared to the single-factor values (age, risk score, gender, and metastasis).…”
Section: Relationship Between the Risk Scores And The Icgsmentioning
confidence: 99%